2021
DOI: 10.1109/access.2021.3109077
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Fluid Characteristics of Microchannel Heat Sink With Multi-Configuration NACA 2412 Hydrofoil Ribs

Abstract: In this study, hydrofoil ribs having NACA 2412 profile were mounted in a novel way at all walls of microchannel heat sink with various configurations to improve its thermo-hydraulic characteristics. The various configurations include comparison between staggered and aligned arrangements, and the variation of rib spacing between two hydrofoils (Sr = 200-600 µm) at a constant cord length (Cr = 400 µm). The performance of various configurations were compared with each other and with smooth channel using parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The effect of trefoil rib configurations on heat transfer and flow characteristics in MCHS were numerically examined and they found that the MC-SWTR configuration performs best with the trefoil ribs mounted on the opposite side wall [19,20]. Shazad et al [21] examined the effect of staggered and aligned configurations of NACA 2412 hydrofoil-shaped ribs on the hydraulic-thermal characteristics of MCHS and discovered that the staggered configuration provides the best overall performance.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of trefoil rib configurations on heat transfer and flow characteristics in MCHS were numerically examined and they found that the MC-SWTR configuration performs best with the trefoil ribs mounted on the opposite side wall [19,20]. Shazad et al [21] examined the effect of staggered and aligned configurations of NACA 2412 hydrofoil-shaped ribs on the hydraulic-thermal characteristics of MCHS and discovered that the staggered configuration provides the best overall performance.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the above passive technique, many researchers have adopted such strategies to enhance the performance of micro-channel heat sink 10 13 . For example, Li et al 14 numerically investigated dimple and pin fin using microchannel heat sinks with water cooling, enhancement of heat transfer, reduction in resistance properties.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to investigate the effect of geometrical parameters of ribs on fluid and heat transfer characteristics of MCHS [20,21]. For example, Khan et al [22] performed numerical simulations to investigate the effect of channel aspect ratio (channel width to height ratio on hydrothermal characteristics of rectangular MCHS.…”
Section: Introductionmentioning
confidence: 99%